2016
DOI: 10.1063/1.4972110
|View full text |Cite
|
Sign up to set email alerts
|

High performance dendrimer functionalized single-walled carbon nanotubes field effect transistor biosensor for protein detection

Abstract: We report a single-walled carbon nanotube (SWNT) field-effect transistor (FET) functionalized with Polyamidoamine (PAMAM) dendrimer with 128 carboxyl groups as anchors for site specific biomolecular immobilization of protein antibody for C-reactive protein (CRP) detection. The FET device was characterized by scanning electron microscopy and current-gate voltage (I-Vg) characteristic studies. A concentration-dependent decrease in the source-drain current was observed in the regime of clinical significance, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Negative cooperativity represents when the binding of a ligand to a specific aptamer receptor makes it more difficult for that aptamer to then bind to other molecules, resulting in the most sensitive responses [ 39 ]. Similar negative cooperativity was also observed by graphene FET aptasensors for detection of cytokine [ 40 ] and thrombin [ 41 ], and CNT FETs to detect protein [ 42 ].…”
Section: Resultssupporting
confidence: 55%
“…Negative cooperativity represents when the binding of a ligand to a specific aptamer receptor makes it more difficult for that aptamer to then bind to other molecules, resulting in the most sensitive responses [ 39 ]. Similar negative cooperativity was also observed by graphene FET aptasensors for detection of cytokine [ 40 ] and thrombin [ 41 ], and CNT FETs to detect protein [ 42 ].…”
Section: Resultssupporting
confidence: 55%
“…In the context of electronic biosensing, carbon-based nanomaterials, nanowires, and nanocomposites have been used as transducing channel materials of FETs for CRP detection. Rajesh et al [ 63 ] developed a polyamidoamine (PAMAM)-modified single-wall carbon nanotube FET for CRP detection. Immobilization with PAMAM dendrimers offers high sensitivity, as they contribute to the high loading and improvement of probe orientation for coupling with CRP biomolecules.…”
Section: Infection-mediated Clinical Biomarkers and Their Electrical Biosensorsmentioning
confidence: 99%
“… ( A ) Electrochemical biosensors: ( a ) origami paper-based sensing of CRP (reprinted with permission from [ 59 ]), ( b ) interdigitated wave-shaped microelectrode-based impedimetric sensor (reprinted from [ 60 ]), ( c ) electrochemical sensing of CRP with ferrocene thiol-coated gold electrode (reprinted from [ 61 ]), and ( d ) sandwich-type sensor with nanohybrid materials for CRP detection (reproduced from [ 62 ]). ( B ) Electronic biosensors: ( a ) PAMAM-modified CNT-based FET (reprinted with permission from [ 63 ]), ( b ) nanowire-based FET (reprinted from [ 64 ]), and ( c ) nanocomposite-based FET for CRP detection (reprinted with permission from [ 65 ]). …”
Section: Figurementioning
confidence: 99%
“…Reported limit of detection is below 0.5 ppm of ammonia gas (NH 3 ). Rajesh et al (2016) reported the fabrication of a single-walled carbon nanotube-based field effect transistor biosensor by employing gold microelectrodes with 3 µm gap on a SiO 2 /Si substrate for the detection of C-reactive protein (CRP) [45]. The SWCNT was functionalized with polyamidoamine (PAMAM) dendrimer with 128 carboxyl groups as anchors.…”
Section: Recent Studies On Cnt-biofetsmentioning
confidence: 99%
“…Despite the numerous advantages as aforementioned, CNTFETs have several limitations such as poor reproducibility due to properties variability of CNTs [40], [72], the hysteresis effect observed upon sweeping the gate voltage back and forth [45], the unselective growth of metallic and semiconducting nanotubes with the limited separation techniques [69], and the nonuniform and increased scattering events in CNT-network-based FET devices due to variations in bundle networks and thus the bulk resistance [52]. However, amongst other issues, the contact issue at the interface between the CNT and the metal electrodes is the most challenging and persisting issue reported by most of the studies in this type of biosensors.…”
Section: Cnt-biofet Sensing Mechanismmentioning
confidence: 99%